Pengaruh Loneliness dan Sensation Seeking terhadap Smartphone Addiction pada Remaja di Surabaya - Anugrah, Eka Rahmadani; Ariana, Atika Dian (Mahesa Research Center, 2023)
This article aims to determine whether there is an influence between loneliness and sensation seeking on smartphone addiction among adolescents in Surabaya. The problem is focused on the excessive use of smartphones which can be caused by loneliness and sensation seeking. In order to approach this problem, a theoretical reference from (Kwon, Kim, Cho, & Yang, 2013). This research used quantitative methods. Subject consist of 101 adolescences in Surabaya. The research data is obtained by using the scale, smartphone addiction scale, loneliness scale, and sensation seeking scale, analyzed by using the multiple regression analysis technique. The results showed that there was a significant influence between loneliness and sensation seeking on smartphone addiction among adolescents in Surabaya (p=0.025<0.05). The contribution value of loneliness and sensation seeking to smartphone addiction is 7.3%. This study illustrates that the higher the loneliness and sensation seeking, the higher the smartphone addiction among adolescents in Surabaya, while the lower the loneliness and sensation seeking, the lower the smartphone addiction.